2008
DOI: 10.1143/jjap.47.3376
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structural Analysis of Diamondlike Carbon Films with Different Electrical Resistivities by X-ray Photoelectron Spectroscopy

Abstract: 6 3.3. Result and discussion ………………………………………………………….. 46 3.3.1. Results of XPS spectrum measurement ……………………….…………. 3.3.2. Results of chemical modification XPS method ………….……………….... 48 3.3.3. Results of contact angle measuremen ……………………………………… 52 3.3.4. Results of zeta potential measurement results ……………………………… 54 3.4. Conclusion ………………………………………………………………………... 56 3.5. References ………………………………………………………………………... 57 "This article was published in Copyright Elsevier (Chapter 4. Introduction of Carboxyl Groups onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 73 publications
0
29
1
Order By: Relevance
“…29 To remove surface contamination, the DLC films were stabilized at 170°C in the chamber before temperature scanning, which was from 170 to 1000°C at a rate of 1°C s −1 . 31 Electrical resistivity measurements were performed using the four-point probe method 13,14 with a vacuum chamber with four metallic probes designed by Seinan Kogyo Co., Ltd. The ion currents were amplified by the SEM with a voltage of 1200 V. The base pressure was below 1 ϫ 10 −9 Torr, and the pressure during heating was maintained below 3 ϫ 10 −8 Torr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 To remove surface contamination, the DLC films were stabilized at 170°C in the chamber before temperature scanning, which was from 170 to 1000°C at a rate of 1°C s −1 . 31 Electrical resistivity measurements were performed using the four-point probe method 13,14 with a vacuum chamber with four metallic probes designed by Seinan Kogyo Co., Ltd. The ion currents were amplified by the SEM with a voltage of 1200 V. The base pressure was below 1 ϫ 10 −9 Torr, and the pressure during heating was maintained below 3 ϫ 10 −8 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…Clues to decompose the spectrum can be obtained by systematically comparing the spectral features taken under different conditions. 13,14 We concluded that the C 1s spectra of the DLC films were decomposed into four chemical components: sp 3 carbon with carbon-carbon bonds ͑C-C sp 3 carbon͒, sp 2 carbon with carbon-carbon bonds ͑C-C sp 2 carbon͒, sp 2 carbon with hydrogen-carbon bonds ͑H-C sp 2 carbon͒, and sp 3 carbon with hydrogen-carbon bonds ͑H-C sp 3 carbon͒. 8 Hydrogen in DLC plays an important role: hydrogencarbon ͑H-C͒ bonds in DLC produce large free spaces in the structure, which inhibit conductive routes and lead to high electrical resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, XPS reveals important bonding information about carbons with nanoscale units such as carbon nanotubes [31], diamond-like carbon films [32], nanostructured carbon films [33], tetrahedral amorphous carbon films [34], amorphous carbon [35], nanoporous carbon [36], activated carbon [37], or carbon black [38]. In addition, XPS is important for the analysis of chemical structure [39], in particular, for the investigation of the sp 2 /sp 3 hybridization ratio [35]. …”
Section: Methodsmentioning
confidence: 99%
“…XPS has been successfully applied to many different carbon materials [121] such as activated carbon [122], carbon spheres [123], amorphous carbon, nanodiamonds [124], diamond-like carbon films [125], carbon nanotubes [126], or nanoporous carbons [127]. Also, it can be used to study processes such as heat and chemical treatment [128], amorphization [129], electrochemical oxidation [130], or structural deformation [131].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%